1988
DOI: 10.1148/radiology.167.3.3283839
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic transplantation: scintigraphy, US, and CT.

Abstract: Twenty-one patients with insulin-dependent diabetes mellitus received simultaneous renal and segmental pancreatic transplants. A retrospective analysis of 112 real-time ultrasound (US) images, 108 technetium-99m glucoheptonate scinti-scans, 55 computed tomography (CT) scans, and 11 cystograms was performed. Complications that were observed included pancreatic transplant rejection, pancreatitis, arteriovenous occlusions, hemorrhage, abscesses, and extravasation at the pancreaticocystostomy site. Scintigraphy is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…After an episode of rejection or venous thrombosis, a new baseline RI must be established. As do other authors, 9 , 13 , 15 , 16 we believe that screening sonography is a useful tool for monitoring pancreatic allografts. On the basis of our findings, we suggest that sonographic examinations be performed in the early postoperative period, whenever complications are suspected, and routinely at 6‐month intervals.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…After an episode of rejection or venous thrombosis, a new baseline RI must be established. As do other authors, 9 , 13 , 15 , 16 we believe that screening sonography is a useful tool for monitoring pancreatic allografts. On the basis of our findings, we suggest that sonographic examinations be performed in the early postoperative period, whenever complications are suspected, and routinely at 6‐month intervals.…”
Section: Discussionsupporting
confidence: 74%
“…The past has seen debate about the role of the RI in pancreas allografts. 2,3,12 Some authors have found sonography 5,6,11,[13][14][15][16][17][18][19][20][21] and the RI 4,9,10,22 to be of value, and others have questioned the utility of the RI in the evaluation of pancreatic allografts. 3,5,12 We have found the RI to be clinically useful.…”
Section: Gimenez Et Al-evaluation Of Pancreatic Allografts With Sonogmentioning
confidence: 99%
“…A decrease in size may be secondary to postransplantation recovery or chronic rejection. Ultrasound provides simple identification of abdominal or pelvic fluid collections [36].…”
Section: Pancreas Transplantationmentioning
confidence: 99%
“…This finding is contrary to several published studies that demonstrated that heterogeneity along with an increase in transplant size were associated with acute rejection. 17,18,22,25 These differing results, however, may reflect differences in the severity of rejection.…”
Section: Discussionmentioning
confidence: 99%